Continuing professional development of expert teacher educators - Hashim, Hashimah (2018)
The purpose of this study was to uncover the teacher educator professional journey since the day they become teacher until they were recognized as expert in teacher education. Research on expertise professional development was extensive, but little attention was explored on how expertise grew over time. Knowledge and expertise acquired by the experts were tacit in nature and difficult to share. To access this, experts need to make their expertise explicit. Therefore, this study explored the teacher educators’ journey along their continuing professional development (CPD) as there was not much study done on expert teacher educator. Underpinning theories of this study covers stages of professional development, reflection in action, tacit knowledge, cognitive analysis and educational psychology. Narrative method was applied in this study, using in-depth, semi-structured interview to highlight how participants negotiate their identities throughout their profession. Seven participants were selected through purposive sampling. Transcribed, observation and document analysis data were used to situate individual experience within participants’ personal experiences to check the similarities and differences in pattern. The framework consists of gathering stories, analyzing them for key elements of the story, and then rewriting the stories to place them within a chronological sequence. The results revealed that there were various pathways the professionals can take in order to become expert. These pathways originated from critical events that occur within their career, eventually lead to the increase in roles and responsibilities of the teacher educators, and the progression of their career. These occurred naturally across the path of the participants’ career, and brought about changes in the person, which motivated them to acquire new knowledge, and changed their attitudes holistically. Participants took pride of their craftsmanship and their realization of self. They become individuals who were involved in deliberate practice, portrayed individual value of their own, acquired leadership through experience, and were in positive environment to develop. The study implicates that a novice needs to undergo long periods of training and practice before they can become experts. It is impossible to shorten the trip, considering the extensive experience which is fundamental to development. Experts can become the role model for professionals in CPD, as they have experienced deliberate practice and have achieved success. Thus, the discovery of this professional development path is important as it provides a model for the juniors to follow. This means that for those who have the intention or ambition to become experts can use them as role models, and follow the professional pathways that the research participants have gone through.